Emerging from the darkness: interplay between light and plastid signaling during chloroplast biogenesis. Issue 3 (12th April 2020) - Hernández‐Verdeja, Tamara; Vuorijoki, Linda; Strand, Åsa
Abstract : Chloroplast biogenesis is a highly complex process that requires carefully coordinated communication between the nucleus and the chloroplast to integrate light signaling and information about the state of the plastid through retrograde signals. Most studies on plastid development have been performed using dark‐grown seedlings and have focused on the transition from etioplast to chloroplast in response to light. Some advances are now also being made to understand the transition directly from proplastids to chloroplasts as it occurs in the shoot apical meristems. Recent reports have highlighted the importance of repressive mechanisms to block premature chloroplast development in dark, both at the transcriptional and post‐transcriptional level. A group of new proteins with dual plastid and nuclear localization were shown to take part in the light triggered degradation of PHYTOCHROME INTERACTING FACTORs (PIFs) in the nucleus and thereby release the suppression of the nuclear photosynthesis associated genes. These dually localized proteins are also required to activate transcription of photosynthesis genes in the plastid in response to light, emphasizing the close link between the nucleus and the plastids during early light response. Furthermore, development of a fully functional chloroplast requires a plastid signal but the nature of this signal(s) is still unknown. GENOMES UNCOUPLED1 (GUN1) is a plastid protein pivotal for retrograde signal(s) during early seedling development, and recent reports have revealed multiple interactors of GUN1 from different plastid processes. These new GUN1 interactors could reveal the true molecular function of the enigmatic character, GUN1, under naturally occurring adverse growth conditions.